2005
DOI: 10.1002/app.22656
|View full text |Cite
|
Sign up to set email alerts
|

Fusion, electrical conductivity, thermal, and mechanical properties of rigid poly(vinyl chloride) (PVC)/carbon black (CB) composites

Abstract: Rigid and conductive poly(vinyl chloride) (PVC)/carbon black (CB) composites were prepared in a Haake torque rheometer. The results illustrate that the fusion torque of the PVC/CB composite is increased as the amount of CB is increased. Both the fusion percolation threshold and the fusion time of PVC/CB composites are decreased when the amount of CB is increased. Two major weight loss stages are observed in the TGA curve of PVC/CB composite. The first thermal degradation onset temperature (T onset1 ) of PVC/CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 17 publications
3
26
0
1
Order By: Relevance
“…The addition of silica or silica-lignin hybrid iller causes a substantial increase in torque, which may be associated with a significant increase in the echanical charging of machines in real processing conditions. Our results agreed well with other reports as regards the influence of particles of SiO2 as well as anocarbon black on the fusion behavior of PVC composites [54,55]. The increased speed of fusion and he increase in the fusion torque of the PVC composites filled with SiO2 and nanocarbon black were xplained by the increase in friction in the system and the increase in the transfer of heat and shear hrough the PVC grains.…”
Section: Polymers 2015 7supporting
confidence: 92%
“…The addition of silica or silica-lignin hybrid iller causes a substantial increase in torque, which may be associated with a significant increase in the echanical charging of machines in real processing conditions. Our results agreed well with other reports as regards the influence of particles of SiO2 as well as anocarbon black on the fusion behavior of PVC composites [54,55]. The increased speed of fusion and he increase in the fusion torque of the PVC composites filled with SiO2 and nanocarbon black were xplained by the increase in friction in the system and the increase in the transfer of heat and shear hrough the PVC grains.…”
Section: Polymers 2015 7supporting
confidence: 92%
“…It was found that the BS values were 16, 15.7, 15.4, 13, 15.2, and 16% decreased from their initial values for 0, 20, 40, 60, 80, and 100% PP content in PVC matrix based composites, respectively. On the other hand, the BM values that were 23,22,20,18,21, and 22% decreased for 0, 20, 40, 60, 80, and 100% PP content in PVC matrix based composites, respectively. From the above results it is clear that the reduction of BS and BM of jute=60% PP þ 40% PVC composite were lower than that of jute=PVC, jute=PP, and other jute=PP þ PVC hybrid composites.…”
Section: Relative Degradation Of the Mechanical Properties Of The Commentioning
confidence: 84%
“…It is a very popular material and has many and varied uses within industry and fabrication applications. Almost all of the studies on PVC=wood-fiber composites have put emphasis on the improvement and up gradation of the fiber and plastic interface, the effect of the nature of the fibers, the impact of processing parameters, and the mechanical properties [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…As we can see, thermal stability of PUs with ILs was a little poorer than that of PUs without ILs. The TGA curve of PUs without ILs shows a one-step decomposition mode with the onset temperature (T ON ) at 299.68C and the end set temperature (T EN ) at 364.98C, due to the decomposition of urethane linkage and the decomposition of soft block in the PUs, respectively [27]. The TGA curve of PU-5.96 show a two-step decomposition: the first (T 1ON ) in the region of 23022608C which could be attributed to the decomposition of urethane bond, and the second (T 2ON ) in the region of 30023808C owing to the decomposition of imidazolium ring and polyols [28].…”
Section: Thermal Properties Analysismentioning
confidence: 99%